DFT combined with XPS to investigate sulfur removal and sulfur-fixation mechanisms of copper oxide during coal pyrolysis and semi-coke combustion. (1st June 2022) - Zhang, Chunjuan; Yan, An; Guo, Huiqing; Lei, Yanqiu; Hao, Haigang; Liu, Fenrong
Graphical abstract: Highlights: CuO shows the superior sulfur fixation ability during coal pyrolysis. Oxygen atmosphere can promote thiophene to decompose on CuO. Experimental results are very consistent with DFT theoretical calculations. Abstract: In this study, Yangquan (YQ) high-sulfur coal was selected to investigate the sulfur-fixation effect of copper oxide (CuO) on H2 S and SO2 and its catalytic effect on the decomposition of thiophene by pyrolysis connected with gas chromatography (Py-GC) and XPS. The mechanisms of sulfur-fixation and thiophene decomposition catalyzed by CuO were investigated by density functional theory (DFT) calculations. After optimization, the stable adsorption configurations of thiophene, H2 S and SO2 on different CuO (1 1 1) surfaces can be obtained. By Py-GC analysis, H2 S release of YQ coal significantly decreases after adding CuO, meanwhile Cu2 S obviously appears in XPS spectra, suggesting CuO possesses the strong sulfur fixation effect on H2 S. This is very consistent with calculated results about stable absorption of H2 S and its easier dissociated reactions whether on the perfect or enriched - oxygen surfaces. However, CuO possesses the weak ability for break SO2 by GC analysis and DFT calculation. But the enriched oxygen can promote CuO to absorb and decompose SO2 . Thiophene is much easier theoretically to decompose under oxygen condition or on the enriched- oxygen CuO (1 1 1) than under Ar atmosphere. This is very consistent with the obvious increasing of thiophene content in XPS spectra of 12% CuO-YQ char and SO2 concentration during different CuO-YQ char combustion. Thus, these experimental results are very in consistence with the DFT theoretical calculations in this study.